Tipos de residuos orgánicos en el ciclo de vida y composición química de larvas de Hermetia sp. “mosca soldado”. Loreto, 2020 - Vásquez Bardales, Joel (2023)
The fly Hermetia illucens is found in nature in a variety of habitats, its larvae consume decaying organic waste. The objective was to determine whether organic waste types influence the life cycle and chemical composition of Hermetia sp. larvae. The study was conducted from May 2020 to May 2021. Two treatments were used (T1: orange waste and T2: banana waste) with 30 replicates. The biological cycle was evaluated in the laboratory at a T° between 26 and 29°C and a RH of 80%, and the periods (days), length and weight of the final larva, prepupa, pupa and adult longevity were recorded. The AOAC method was used to analyze the chemical composition of the larvae. The biological cycle of H. illucens with orange lasted 64.02 days and 88.97 days with plantain, both had 97% larval survival. In prepupae and pupae, survival was lower with plantain. There were no significant differences in the length of prepupae and pupae larvae (p>0.05). Neither in the larva and pupae weight variable (p>0.05). There was a highly significant difference in the prepupal stage (p=0.003). The chemical composition revealed that the larvae nourished with plantain had a higher percentage of lipids, proteins, crude fiber and carbohydrates.